New Perspectives in Psychopathology - Telles-Correia, Diogo; Cheniaux, Elie (Frontiers Media SA, 2020)
Nowadays, important challenges are posed to psychiatry and psychology. These are in the domain of neurosciences, since the neurobiological correlates of the symptoms and psychiatric disorders are far from what was intended, but also of clinical order because of a progressive increase of the diagnostic categories in the diagnostic manuals, or therapeutical, ethical, social and legal ones. It is urgent, therefore, to reflect on these aspects, rather than continue to replicate the same paradigms.